THE EFFECT OF WORK ENVIRONMENT AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS INTERVENING VARIABLE AT PT SUKSES ARTHA MULIA - Dian Octavia Handayni; M. Havidz Aima (Dinasti Publisher, 2021)
This research has purposes to discover and analyze furture relates the effect of work environment and compensation on employee performance with motivation as an intervening variable at PT Sukses Artha Mulia. The research method used a quantitative research with a causal method. The population and sample in this research amounted to 109 respondents who are employees at PT Sukses Artha Mulia. The data analysis method used SEM-PLS. And the results of the research indicate that the work environment has no significant effect on motivation. Compensation has a significant effect on motivation. The work environment has no significant effect on employee performance. Compensation has a significant effect on employee performance. Motivation has a significant effect on employee performance. Work environment and compensation simultaneously affect motivation. Work environment, compensation, and motivation simultaneously affect employee performance. Motivation has no effect in mediating the work environment on employee performance. However, motivation has a partial effect in mediating compensation on employee performance.